2011
DOI: 10.1158/1078-0432.ccr-10-1920
|View full text |Cite
|
Sign up to set email alerts
|

HER2 Protein and Gene Variation between Primary and Metastatic Breast Cancer: Significance and Impact on Patient Care

Abstract: Purpose: To analyze HER2 status in primary breast cancer (PBC) compared with correspondent metachronous metastases and to investigate whether BC phenotype may be predictive of change in HER2 expression.Experimental Design: HER2 was investigated by immunohistochemistry, silver in situ hybridization (SISH), and FISH, in a series of 137 tumors, building up a tissue microarray to concurrently analyze each single PBC and metastatic (MBC) on the same slide.Results: HER2 status was discordant in 14 cases (10%): 12 ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 29 publications
3
48
0
2
Order By: Relevance
“…[8][9][10] However, several studies have reported significant discordance. [11][12][13][14] Some studies have suggested that HER2 gene amplification can be acquired during tumor progression and that this could be a cause of this discordance. 12,13 Others have demonstrated primary intratumoral heterogeneity of both HER2 expression and HER2 gene amplification.…”
mentioning
confidence: 99%
“…[8][9][10] However, several studies have reported significant discordance. [11][12][13][14] Some studies have suggested that HER2 gene amplification can be acquired during tumor progression and that this could be a cause of this discordance. 12,13 Others have demonstrated primary intratumoral heterogeneity of both HER2 expression and HER2 gene amplification.…”
mentioning
confidence: 99%
“…A separate study of 137 primary breast tumours and metachronous metastases revealed discordant her2 status in only 10% of cases (n = 14). Given that some of the patients had received prior trastuzumab, it is interesting to note that a pairing of her2-negative primary tumour with her2-positive metastasis was significantly more common than was her2-positive primary tumour with her2-negative metastasis (12 cases vs. 2 cases, p = 0.04) 48 . However, no dedicated analysis was performed to assess the stability of her2 status according to trastuzumab pretreatment.…”
Section: Retesting Metastases In Patients Pretreated With Chemotherapmentioning
confidence: 99%
“…However, this can be intricate as HER2 expression may vary through progression from primary to secondary disease with locoregional and distant recurrences often not being amenable to biopsy (11). Furthermore, recent studies have highlighted spatial heterogeneity as a potential source of incorrect assessment (12).…”
Section: Introductionmentioning
confidence: 99%